2017
DOI: 10.1007/s10393-017-1245-x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Fluctuations of Astrovirus, But Not Coronavirus Shedding in Bats Inhabiting Human-Modified Tropical Forests

Abstract: Emerging infectious diseases (EIDs) are considered a major threat to global health. Most EIDs appear to result from increased contact between wildlife and humans, especially when humans encroach into formerly pristine habitats. Habitat deterioration may also negatively affect the physiology and health of wildlife species, which may eventually lead to a higher susceptibility to infectious agents and/or increased shedding of the pathogens causing EIDs. Bats are known to host viruses closely related to important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 80 publications
(117 reference statements)
2
47
2
Order By: Relevance
“…Previous surveillance efforts have demonstrated variable rates of astrovirus infection from diverse bat species, including those tested here [38]. Astroviruses have been detected from ten other species of Rhinolophus bats in previous studies [39][40][41][42][43]. A recent study in Cambodia and Laos screened six members of the family Pteropodidae and astroviruses were only detected in Eoncyteris spelaea (3.8%) and Rousettus spp.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Previous surveillance efforts have demonstrated variable rates of astrovirus infection from diverse bat species, including those tested here [38]. Astroviruses have been detected from ten other species of Rhinolophus bats in previous studies [39][40][41][42][43]. A recent study in Cambodia and Laos screened six members of the family Pteropodidae and astroviruses were only detected in Eoncyteris spelaea (3.8%) and Rousettus spp.…”
Section: Discussionmentioning
confidence: 77%
“…We found variable rates of shedding across our sampling period. In Singapore, temperatures are not variable month to month, but there are two monsoon seasons, which may be associated with bat borne virus shedding [43]. A study on Myotis myotis in Germany demonstrated distinct astrovirus amplification peaks that correlated with the formation of a suitable roost size and also a post-parturition period [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Seltmann et al . ). Specifically, nutritional stress after loss of winter nectar sources may drive Hendra virus shedding and spillover from fruit bats (Plowright et al .…”
Section: Discussionmentioning
confidence: 97%
“…Increasing evidence supports the assumption that habitat quality and bat health are inherently linked. For example, in paleotropical forests with intense logging and fragmentation, bats with poor body conditions were more likely to shed astroviruses in feces [34]. Seltmann et al [34] speculated that increased susceptibility of individuals to acquire and shed viruses may have resulted from stress-induced immunosuppression.…”
Section: Human-cave Bat Interactionsmentioning
confidence: 99%